A guide to supramolecular polymerizations. Issue 6 (9th January 2020) - Hartlieb, Matthias; Mansfield, Edward D. H.; Perrier, Sebastien
Abstract : Supramolecular polymers are non-covalent assemblies of unimeric building blocks connected by secondary interactions and hold great promises due to their dynamic nature. Abstract : Supramolecular polymers or fibers are non-covalent assemblies of unimeric building blocks connected by secondary interactions such as hydrogen bonds or π–π interactions. Such structures hold enormous potential in the development of future materials, as their non-covalent nature makes them highly modular and adaptive. Within this review we aim to provide a broad overview over the area of linear supramolecular polymers including the different mechanisms of their polymerization as well as methods essential for their characterization. The different non-covalent interactions able to form supramolecular polymers are discussed, and key examples for each species are shown. Particular emphasis is laid on the development of living supramolecular polymerization able to produce fibers with a controlled length and low length dispersity, and even enable the production of supramolecular block copolymers. Another important and very recent field is the development of out-of-equilibrium supramolecular polymers, where the polymerization process can be temporally controlled enabling access to highly adaptive materials.